Microstructural Characteristics, Mechanical and Corrosion Properties of an Extruded Low-Alloyed Mg-Bi-Al-Zn Alloy - Cheng, Wei-li; Liu, Yan-hui; Ma, Shi-chao; Wang, Li-fei; Wang, Hong-xia; Niu, Xiao-feng (Frontiers in Materials, 2020)
An extruded low-alloyed Mg-0.97 Bi-0.96 Al-0.98 (wt%) Zn alloy combining excellent tensile property (YS = 201 MPa, EL = 29.4%) with high corrosion resistance (Pi = 0.14 mm/a) for biomedical application is successfully extruded in the study. The extruded alloy is mainly composed of dynamic recrystallized (DRXed) grains (2.32 ± 0.12 μm) and strongly textured coarse non-DRXed grains as well as certain nano-scaled Mg3Bi2 precipitates (135.68 ± 27.86 nm).Note that most basal planes for non-DRXed grains are distributed parallel to extrusion direction preferentially. The study explored dependences of properties and relevant mechanisms of the studied alloy on its microstructural characteristics in terms of grain size, grain orientation, precipitates and /or the corrosion products film.